2000
DOI: 10.1007/s11906-996-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and current issues in compliance and patient outcomes

Abstract: Economic and human costs associated with untreated or inadequately controlled hypertension and its complications continue to be an issue in the United States despite the availability of numerous antihypertensive agents. Knowledge of hypertension, product profiles, tolerability concerns, convenience of dosing, health-related quality of life effects, and cost of therapy are some of the factors that may influence the compliance of patients to their medication regimens. Recent reports on patient noncompliance have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 23 publications
0
26
1
Order By: Relevance
“…Research has generally found that medication barriers are highly associated with poor medication adherence (Allen, 1998;Clark, 1991;Richardson, Simons-Morton, & Annegers, 1993;Zyczynski & Coyne, 2000). Medication barriers often encompass patient specific barriers such as forgetfulness, beliefs, and attitudes but can also encompass barriers that are medication specific, disease specific, or logistic (Bosworth, 2005;Ogedegbe, Harrison, Robbins, Mancuso, & Allegrante, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Research has generally found that medication barriers are highly associated with poor medication adherence (Allen, 1998;Clark, 1991;Richardson, Simons-Morton, & Annegers, 1993;Zyczynski & Coyne, 2000). Medication barriers often encompass patient specific barriers such as forgetfulness, beliefs, and attitudes but can also encompass barriers that are medication specific, disease specific, or logistic (Bosworth, 2005;Ogedegbe, Harrison, Robbins, Mancuso, & Allegrante, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, despite the expanding choices in antihypertensive treatments, less than one-third of hypertensive adults have their BP adequately controlled in the United States. 4 In Malaysia, the Second National Health Morbidity Survey reported that the prevalence of hypertension among adults aged 30 years and above was 29.9%, of whom 32.6% had stopped treatment since diagnosis. The main reasons given for noncompliance are predominantly based around poor communication.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found this to be one of the 319 most effective strategies for improving adherence to medications particularly for unintentional 320 non-adherence related to forgetfulness or confusion. 2,19,33 In Australia, community pharmacists The "number of full time equivalent staff' was found to be significantly associated with 405 pharmacists' provision of strategies used to support adherence. Perhaps this is not surprising as 406 pharmacists who have adequate number of pharmacy technicians may be able to spend more 407 time with patients to provide adherence support, or those who are oriented to providing 408 professional services ensure that they are adequately staffed".…”
mentioning
confidence: 99%